Lex Certa and Criminalization Expansion in Article 12B of Law No. 5 of 2018 - Mukhlissuddin; Ayub Torry Satriyo Kusumo (Lambung Mangkurat Law Journal, 2026)
This study analyzes the expansion of criminalization in Article 12B of Law Number 5 of 2018, particularly the inclusion of information and communication technology–based training as a criminal offense. The central legal problem addressed in this research concerns the ambiguity of normative boundaries in defining “training” within the digital context, which potentially undermines legal certainty and opens room for arbitrary law enforcement. The process of digitalization complicates the enforcement of Article 12B, as online activities related to knowledge sharing, expression, and association increasingly overlap with constitutionally protected civil liberties.Employing a normative juridical research method, this study examines statutory provisions, constitutional principles, and relevant human rights doctrines to assess the compatibility of Article 12B with the 1945 Constitution of the Republic of Indonesia. The analysis focuses on the principle of lex certa as an essential element of criminal law and its function in safeguarding freedom of expression and freedom of association in the digital era. The findings indicate that the expanded formulation of Article 12B lacks sufficient normative clarity, thereby creating tension between state security objectives and constitutional guarantees of human rights. This study concludes that, without strict interpretative limitations, Article 12B risks constitutional inconsistency, particularly with Articles 28E and 28G of the 1945 Constitution. Therefore, normative refinement and constitutional-oriented interpretation are necessary to ensure that counter-terrorism policies remain proportionate, legally certain, and aligned with human rights standards in the digital era.